STUDY ON THE CURRENT REGIME IN PHAN THIET BAY USING 3D NONLINEAR FINITE ELEMENT METHOD - Long, Bui Hong; Chung, Tran Van (Vietnam Journal of Marine Science and Technology, 2012)
Different types of currents (residual-, tidal-, wind- and general currents, etc.) in Phan Thiet bay have been studied using 3D nonlinear finite element method (FEM). The studied results showed the applicability of FEM for simulation of current regime in waters with complex topography and large liquid boundary. To evaluate the applicability of the model, we calculated separately the 5 main current constituents M2, S2, K1, O1, N2 of tidal currents. Then the harmonic constants of these current constituents were compared with data collected from Phan Thiet water level station. According to the comparison results, the absolute differences are as follows: the amplitude was max 3.1 cm (constituent M2), min 0.0 cm (exact constituent S2), the tidal phase was max 13.90(constituent K1) and min 3.80 (constituent S2). In the surface layer, during northeast monsoon period, the horizontal wind currents may reach its max speed of 85.3cm/s, direction 185.70 around the position (108.05540E; 10.70140N); but the peak horizontal speed of the general currents can reach 60.6cm/s, direction 209.60, around position (108.08200E; 10.70150N). During southwest monsoon period, max speed of the horizontal wind currents reaches 53.0cm/s, direction 10.30; position (108.1086E; 10.70150N), whereas, general current was 36.6cm/s, direction 23.80; position (108.03550E; 10.70540N). These study results are the first 3D nonlinear calculation results for the currents in Phan Thiet bay. These results have shown the possibility of detailed study of current distribution and finding out positions with particular current distribution in this area, providing scientific base and reliable information for a reasonable development planning.